La interculturalidad y la convivencia escolar en estudiantes de Educación General Básica - Estrella Agila, Sabrina Paola (2023)
The proposed research addresses the conflicts that may arise during school life in ninth-year students of Basic General Education in the evening session of the Nelson Mateus Macias Complete Basic Education School in the city of Guayaquil. The general objective was to strengthen interculturality for the school coexistence in the students as specific objectives, the referents and theoretical foundations about interculturality and school coexistence will be identified, another was to diagnose the current state of children on interculturality and school coexistence and the third design workshops as a didactic guide oriented to the strengthening of interculturality for healthy school coexistence in the students of said educational institution. This research is based on a field study of students, authorities and the rest of the educational community through a survey which measured Interculturality and School Coexistence, it was possible to conclude that modern society is resistant when it comes to welcoming students. the cultural diversity, to which some of the students belong, for which values must be reinforced so that cooperative learning and this will generate acceptance and respect for other people.